The Role of Christian Education in Building Spiritual Resilience Among Adolescents Amid Peer Influence - Amirrudin Zalukhu (International Journal of Christian Education and Philosophical Inquiry, 2025)
This qualitative literature review examines the role of Christian education in building spiritual resilience among adolescents amid peer influence. Spiritual resilience is defined as the ability to maintain one's faith and moral values in the face of external influences during adolescence, particularly peer pressure. Through an analysis of existing studies, the review explores how Christian education helps adolescents develop a strong spiritual foundation, providing them with tools to resist negative peer influences and make ethical decisions. The study highlights key factors such as the role of faith-based communities, family involvement, and consistent spiritual guidance in nurturing resilience. The review also emphasizes the importance of creating supportive environments within Christian educational settings, where adolescents can reflect on their beliefs, engage in positive peer relationships, and grow in their faith. It identifies both supporting and hindering factors that influence spiritual resilience, suggesting that effective Christian education programs can foster healthy moral and emotional strength..